GENDERED HERITAGE: A STUDY OF BODO WOMEN’S ROLE IN PRESERVING CULTURAL TRADITIONS - Basumatary, Junmani (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The Bodo are an ethnic and linguistic aboriginal tribe of Assam and have a unique culture and linguistic traits. The Bodo culture is multifaceted and has rich tangible and intangible heritage that are deeply rooted in their socio-cultural identity. Consequently, social norms and traditions are very important to the Bodo’s way of life. Through intangible heritage like: rituals, customs, beliefs, storytelling, and group activities Bodo women serve as stewards of their cultural legacy. It is therefore, Bodo women are seen as carrier and preserver of intangible heritage (cultural practices) from generation to generation. This paper examines how Bodo women fit themselves within the framework of cultural preservation, emphasizing their role in social gatherings, traditional events, and family systems (belief/customs). The study is descriptive and qualitative in type and approach. Data have been drawn from the Secondary sources.